Experimental and Finite Element Studies on CFF Strengthened RC Rectangular Beams in Shear - Jayaprakash, J. (International Journal of Integrated Engineering, 2015)
This paper presents the experimental and finite element (FE) results of Reinforced Concrete (RC) rectangular beams in shear bonded externally using Carbon Fibre Fabric (CFF) reinforcement.  In the experimental study, all, except control, beams were strengthened/repaired with CFF reinforcement at laboratory environment.  These beams were tested under four point bending system for failure.  Moreover, to validate the obtained experimental results, the study used two-dimensional model to simulate the shear behaviour of the CFF repaired/strengthened beams using LUSAS finite element analysis software.  The experimental results confirm that the CFF repaired and initially strengthened beams attained a gain of 37.28% - 77.95% and 60.71% - 77.34% for shear span to effective depth ratio of 2.5 and 4.0, respectively.  The results of FE prediction were compared against the experimental results obtained from the experimental investigation.  It was generally found that the comparison between the predicted FE and experimental results show satisfactory correlation in terms of load-displacement profile.